Cryptosporidium and Giardia infections of lambs in Southwest Norway: a longitudinal study - Tsegabirhan Kifleyohannes; Elin Skorpen; Kine Rosnes Hansen; Snorre Stuen; Lucy J. Robertson (Acta Veterinaria Scandinavica)
Abstract Background Domestic ruminants are common hosts of Cryptosporidium spp. and Giardia spp. Although both protozoan parasites are known to circulate among lambs in Norway, their epidemiology is largely unknown. This longitudinal study investigated the occurrence of both parasites in different age groups of lambs, with molecular characterisation of some isolates. Faecal samples (n = 394) were collected from lambs from 17 different flocks on three occasions. At first sampling, lambs were approximately 2–3 days old, and 160 samples were collected. On the two subsequent occasions, no additional lambs were included and samples collected were from among the lambs sampled on the first occasion. At second sampling, lambs were 14–21 days old, and 134 samples were collected. At the final sampling, lambs were 40–42 days old, and 100 samples were collected. Samples were analysed using immunofluorescent antibody staining (IFAT), with molecular characterisation of selected positive samples by PCR and sequencing. Results In total, 66 samples (17%) were positive for Cryptosporidium oocysts and 61 (16%) positive for Giardia cysts by IFAT. Cryptosporidium was detected most often at the second sampling, occurring significantly more often than in younger lambs (P < 0.0001). Longitudinal investigation indicated that around 20% of lambs shedding Cryptosporidium oocysts at one sampling occasion were still infected, or had been reinfected, at the next sampling occasion. A significant increase in Giardia infection occurred with age, with a higher occurrence at the second sampling occasion than the first (P < 0.0001), and a greater occurrence at the third sampling occasion than both the first (P < 0.0001) and second (P = 0.052). For Giardia, persistent infection, or reinfection between sampling occasions, was between 25 and 40%. Associations were detected between infection status and location (Vestland or Rogaland), infection status and diarrhoea, and intensity of infection and diarrhoea. Molecular methods identified two species of Cryptosporidium (C. parvum (subtypes IIaA13G1R2 (4 samples) and IIdA20G1 (1 sample)) and C. ubiquitum, subtype XIIa (3 samples). Giardia isolates were identified as G. bovis (G. duodenalis, Assemblage E). Conclusions Cryptosporidium and Giardia infections occurred commonly in lambs in the three different age groups, with more positives detected at the second and third sampling (when the lambs were older) than at the first. As some lambs were positive for one or other of the parasites on two sampling occasions, prolonged infection or reinfection may occur. Molecular characterisation indicated that although the Cryptosporidium in these lambs can be of public health importance, the Giardia species identified are not considered zoonotic.